Validation of the inventary of emotional capacities in adolescents (ICEA) - Zoe Bello Dávila; Alina Alfonso León; Jenfifer Medina García (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2021)
Background: given the characteristics of adolescence where important changes occur not only at a physiological level but also at a psychological level, emotional capacities acquire great relevance. These allow for greater psychological adjustment and well-being, higher quality in interpersonal relationships, better school performance and fewer disruptive behaviors, depression and anxiety. Objective: Build and validate the Inventory of Emotional Capacities in Adolescents. Methods: The investigation was carried out in two stages; 419 adolescents and 9 experts participated in the first, who assessed the content and construct validity of the instrument. In the second stage, with a sample of 291 adolescents, the concurrent criterion validation of the ICEA was carried out with the measures of Psychological Well-being (BIEPS-J), with the Trait-State Anxiety Inventory (IDARE-N) and the Trait Depression Inventory -State (IDERE-N). Results: From the judgment of experts and the factor analysis, an instrument of 43 items is obtained with a multidimensional structure of 5 factors, which correspond to the emotional capacities described in the Goleman model: self-knowledge, self-control, self-motivation, empathy and relationship management. Positive and moderate correlations are obtained with the BIEPS-J scale; negative and moderate with the IDARE-N, negative and moderate with depression as a trait and negative and weak with depression as a state. Internal consistency is high (Cronbach's Alpha = .86) Conclusions: The construction of a measure of evaluation of emotional capacities in adolescents is achieved that has content, construct and criterion validity, as well as high reliability and internal consistency.